PENGARUH ATTITUDE TOWARD BEHAVIOR, SUBJECTIVE NORM, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP INTENSI MENJADI SEORANG ENTREPRENEUR PADA MAHASISWA PESERTA MATAKULIAH ENTREPRENEURSHIP 1 DAN 2 BATCH 2017 - Haris Herdiansyah, S.Psi., M.Si. (President University, 2020)
The aim of this study was to see the influence of attitude toward behavior (ATB), subjective norm (SN), and perceived behavioral control (PBC) on the intention to become an entrepreneur for student participants in entrepreneurship courses 1 and 2 batch 2017. Theoretically, the more the stronger the three determinants of intention then intention will be easier to manifest into behavior. The stronger entrepreneurship courses 1 and 2 are given, the tendency of intention to become an entrepreneur will be stronger. The alternative hypothesis proposed is that there is an influence of ATB, SN, and PBC on the intention to become an entrepreneur in the students participating in entrepreneurship courses. 276 students of entrepreneurship 1 and 2 are involved and obtained through purposive sampling techniques, data collection instruments in the form of questionnaires consisting of 30 items, data analysis techniques used using multiple regression analysis techniques with 3 predictors . The results found that the determinant of ATB and SN significantly influence the intention to become an entrepreneur, while the PBC determinant does not significantly influence the intention to become an entrepreneur in student participants in entrepreneurship courses 1 and 2 batch 2017 Kata Kunci: Attitude toward behavior, subjective norm, perceived behavioral control, intensi, entrepreneur, mahasiswa, matakuliah entrepreneurship